Effects of a Moderate Physical Training on the Leptin Synthesis by Adipose Tissue of Adult Rats Submitted to a Perinatal Low-protein Diet - de Mélo Montenegro, I.H. P.; Moita, L.; dos Reis, F.K. W.; de Oliveira, E.; Lisboa, P. C.; de Moura, E. G.; Manhães-de-Castro, R.; Leandro, C. G. (Hormone and Metabolic Research, 2012)
The aim of the study was to verify if moderate physical training affects leptin content in visceral and subcutaneous adipose tissue of adult rats subjected to a low-protein diet during the perinatal period. Male Wistar rats were divided into 2 groups according to their mother’s diet during gestation and lactation: control (17% casein, C, n=12) and low-protein (8% casein, LP, n=12). On postnatal day 60, half of each group was submitted to moderate physical training (8 wks, 5 d · wk − 1, 60 min · d − 1, at 70% of VO2max, T) or not. After the physical training period, visceral and subcutaneous adipose tissues were removed. Leptin content was evaluated by western blotting. Starting from the fifth week on, T pups showed a reduction in the body weight. Similarly, LP+T offspring showed a lower body weight starting from the sixth week on. Western blotting analysis showed that leptin content in the visceral tissue was higher in the LP rats (p<0.01) and it was reversed in LP+T. No difference was found in the subcutaneous tissue. Moderate physical training attenuated the effects of a perinatal low-protein diet on the leptin content in visceral adipose tissue in adult offspring.
Keywords: perinatal undernutrition; physical exercise; programming; leptin; visceral adipose tissue